The knowledge of ignorance (Polis (Santiago), 2018)
The author contrasts Socrates with the new scientists, pointing out that today we must continue to build our philosophy of knowledge over the thesis of our lack of knowledge, in defense of tolerance and ethical principles. He proposes then a new professional ethics -contrasting it with the old professional ethic- built on the basis of twelve principles, which he develops in this text.
Keywords: Socrates; scientists; philosophy of knowledge; professional ethics